Characterization and potential roles of calretinin in rodent spermatozoa. (September 2018) - Dressen, Cindy; Schwaller, Beat; Vegh, Grégory; Leleux, Fabienne; Gall, David; Lebrun, Philippe; Lybaert, Pascale
Graphical abstract: Highlights: Calretinin was detected in the sperm principal piece. Sperm motility parameters were modified in the absence of calretinin (CR −/− mice). The fertility of CR −/− mice was reduced compared to wild-type mice. Abstract: Calretinin has been detected in various excitable cells but the presence and putative roles of such a calcium-binding protein has never been characterized in sperm. Epididymal spermatozoa were collected from C57Bl6 (wild-type, WT) or calretinin knockout ( CR −/− ) mice and Wistar rats. A specific staining for calretinin was detected by immunofluorescence in the principal piece of the flagellum, both in WT mouse and rat spermatozoa. Western blots confirmed the expression of calretinin in rat and WT spermatozoa as well as its absence in CR −/− mice. No significant difference was observed in the spontaneous acrosome reaction between WT and CR −/− sperm. The addition of the calcium-ionophore A-23187, Thapsigargin or Progesterone to WT or CR −/− incubated spermatozoa induced increases in the acrosome reaction but the stimulatory effects were identical in both genotypes. Motility measurements assessed by computer-assisted sperm analysis indicated that, under basal non-stimulatory conditions, CR -/- sperm exhibited a lower curvilinear velocity and a smaller lateral head movement amplitude, although no difference was observed for the beat cross frequency. After incubation with 25 mM NH4 Cl, the curvilinear velocity, the amplitude of the lateral head movement and the hyperactivation were increased, while the beat cross frequency was decreased, in both genotypes. Evaluation of the in vivo fertility potential indicated that the CR −/− litter sizes were clearly reduced compared to the WT litter sizes. Our study describes, for the first time, the expression of calretinin in sperm. These data extend the potential implication of calcium-binding proteins in the sperm calcium-signaling cascade and bring new insights into the understanding of sperm physiology.